Developing Mathematical Problem-Based Learning Devices on Social Aritmetic Topic to Improve Creative Thinking Skills of Junior High Schools Students - Chrisdiyanto, Endar; Alfian, Zudhy Nur; Pangestu, Aji (Proceeding International Conference on Science and Engineering, 2020)
The objective of this development research is to produce a mathematical problem-based learning tool on the topic of social arithmetic to improve the creative thinking skills of junior high school students. This research describes the quality of the learning tools developed in terms of three aspects, namely validity, practicality, and effectiveness. The development model employed in the development of this learning device is the ADDIE model. The ADDIE model consists of analysis, design, development, implementation, and evaluation. Learning devices meet the validity criteria indicated by the lesson plan score of 151 in the very good category. The assessment score of student’s worksheet is 125 which is in a very good category. Teacher questionnaire responses obtain a score of 87 which is in the very practical category and the student response questionnaire obtains a score of 68.29 which is in the very practical category. The results of the analysis on the effectiveness show that the learning device meets the effectiveness criteria viewed from the percentage of completeness of 87%, the significance value of 0,000 <? (0.005), and the value of t count (6,604)> t table (1,645).